2014
DOI: 10.1111/tops.12123
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, Cultural, and Linguistic Sources of a Handshape Distinction Expressing Agentivity

Abstract: In this paper the cognitive, cultural, and linguistic bases for a pattern of conventionalization of two types of iconic handshapes are described. Work on sign languages has shown that handling handshapes (H-HSs: those that represent how objects are handled or manipulated) and object handshapes (O-HSs: those that represent the class, size, or shape of objects) express an agentive/non-agentive semantic distinction in many sign languages. H-HSs are used in agentive event descriptions and O-HSs are used in non-age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 47 publications
7
47
0
Order By: Relevance
“…Previously, we distinguished between the h a n d l i n g strategy (as in Figure 3a), where the signer's hand represents a human hand in action, and i n st r u m e n t strategy (as in Figure 3b), where the signer's hand additionally profiles the shape of the referent tool (Padden et al, , 2015. Our distinction between the two iconic strategies can also be found in work by others (Goodglass & Kaplan, 1963;Overton & Jackson, 1973;Boyatzis & Watson, 1993;O'Reilly, 1995;Brentari et al, 2012Brentari et al, , 2015. Here, we collapse the two strategies together as m a n i p u l at i o n to highlight their common property, that the signer's body represents the body of a human agent using the referent, and that the form includes motion of the signer's arm representing human action.…”
Section: Overview Of the Studiesmentioning
confidence: 87%
See 3 more Smart Citations
“…Previously, we distinguished between the h a n d l i n g strategy (as in Figure 3a), where the signer's hand represents a human hand in action, and i n st r u m e n t strategy (as in Figure 3b), where the signer's hand additionally profiles the shape of the referent tool (Padden et al, , 2015. Our distinction between the two iconic strategies can also be found in work by others (Goodglass & Kaplan, 1963;Overton & Jackson, 1973;Boyatzis & Watson, 1993;O'Reilly, 1995;Brentari et al, 2012Brentari et al, , 2015. Here, we collapse the two strategies together as m a n i p u l at i o n to highlight their common property, that the signer's body represents the body of a human agent using the referent, and that the form includes motion of the signer's arm representing human action.…”
Section: Overview Of the Studiesmentioning
confidence: 87%
“…All participants in the Gesture group were tested in a monolingual spoken English setting and reported that they had no knowledge of a sign language. We acknowledge that testing groups of homogeneous speakers of different languages, as reported in Padden et al (2013) and Brentari et al (2015), could be a future extension for more in-depth understanding of cross-cultural variation in gesture patterns. However, such a goal is beyond the scope of the present study.…”
Section: Overview Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purposes of this paper, I reduce Müller's four modes of representation to two, h a n d s r e p r e s e n t i n g h a n d s and h a n d s r e p r e s e n t i n g e n t i t i e s ( see Brentari, Coppola, Mazzoni, &Goldin-Meadow, 2012, andBrentari et al, 2014, for use of similar terminology). Following the approach taken by Alibabli (2008, 2010), I assume that there is a link between type of imagery and different types of gestures.…”
Section: Describing Gestur Al Elementsmentioning
confidence: 99%